‘Knowing about Knowing and Learning about Learning’ : Metacognitive Awareness as a Predictor of Academic Achievement - Rai, Kathryn; Singh, Rajinder (JOURNAL OF INDIAN EDUCATION, 2024)
This paper studied the metacognitive awareness and academic achievement of science and humanities students. Metacognitive awareness has been investigated with special reference to its components, i.e., knowledge of cognition and regulation of cognition, which are further divided into three and five subcomponents, respectively. Data has been collected from 490 Grade 12 school students. The major findings indicated that metacognitive awareness varies significantly between males and females with respect to the sub-components declarative knowledge, procedural knowledge, information management strategies, debugging strategies and planning but not on the overall MAI scores. Also, the results revealed that science students possess better metacognitive awareness than humanities students, with their scores being significantly higher in procedural knowledge and planning. The correlation analysis showed that there is a strong association between metacognitive awareness and academic achievement and the prediction analysis showed that metacognitive awareness can be a significant predictor of academic achievement. This study alerts the teaching community to the necessity of helping students develop metacognitive components and teaches them how to recognise themselves as learners. In order to frame teaching-learning settings appropriately, more study on the metacognitive awareness of students from various academic streams is also necessary.